2019
DOI: 10.1111/tpj.14560
|View full text |Cite
|
Sign up to set email alerts
|

The influence of stomatal morphology and distribution on photosynthetic gas exchange

Abstract: Summary The intricate and interconnecting reactions of C3 photosynthesis are often limited by one of two fundamental processes: the conversion of solar energy into chemical energy, or the diffusion of CO2 from the atmosphere through the stomata, and ultimately into the chloroplast. In this review, we explore how the contributions of stomatal morphology and distribution can affect photosynthesis, through changes in gaseous exchange. The factors driving this relationship are considered, and recent results from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(150 citation statements)
references
References 104 publications
(163 reference statements)
4
120
0
6
Order By: Relevance
“…Stomatal density and size set the upper limit on gas exchange in leaves (Harrison et al, 2019) and is often closely related to operational stomatal conductance in nature (Murray et al, 2019). Despite the fact that many foliar pathogens infect through stomata, the relationship between stomatal anatomy and resistance to foliar pathogens is less clear than it is for gas exchange.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stomatal density and size set the upper limit on gas exchange in leaves (Harrison et al, 2019) and is often closely related to operational stomatal conductance in nature (Murray et al, 2019). Despite the fact that many foliar pathogens infect through stomata, the relationship between stomatal anatomy and resistance to foliar pathogens is less clear than it is for gas exchange.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the physical relationship between stomatal size, density, and conductance is well-established (Harrison et al, 2019). Size and density also likely affect the probability of pathogen colonization, but we do not have a theoretical model that makes quantitative predictions.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…It has been shown that changes to stomatal size and density can be correlated with g s , and so it follows that genetic manipulation of SD has the potential to increase photosynthetic gas exchange (Franks et al, 2012). However, as pointed out by Harrison et al (2019), such a coupling between SD and gas exchange does not always exist in practice. Nevertheless, Arabidopsis EPFL9overexpressing plants (with~600% increased SD) show enhanced A at both ambient and elevated CO 2 , probably due to a much increased g s (Tanaka et al, 2013).…”
Section: Can Increases To Stomatal Density Improve Photosynthetic Effmentioning
confidence: 99%
“…The triple MAPK BdYODA was shown to be involved in maintaining fate asymmetry, and bdyda mutant plants showed clustered stomata, prickle hair cells and silica cells within but never between cell files (Abrash et al, 2018). Furthermore, overexpression of EPF1 in barley, rice and wheat drastically reduced stomatal density and resulted in more drought-resistant plants (for review, see Hughes et al, 2017;Caine et al, 2018;Bertolino et al, 2019;Dunn et al, 2019;Harrison et al 2019;Lu et al, 2019). Similarly, CRISPR/Cas9-editing of the stomatal fate promoting OsEPFL9/OsSTOMAGEN lead to an eightfold decrease in stomatal density in rice leaves (Yin et al, 2017).…”
Section: The One-cell-spacing Rulecontrol Of Stomatal Patterning and mentioning
confidence: 99%